2014
DOI: 10.1016/j.ajhg.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Truncating and Missense Mutations in IGHMBP2 Cause Charcot-Marie Tooth Disease Type 2

Abstract: Using a combination of exome sequencing and linkage analysis, we investigated an English family with two affected siblings in their 40s with recessive Charcot-Marie Tooth disease type 2 (CMT2). Compound heterozygous mutations in the immunoglobulin-helicase-μ-binding protein 2 (IGHMBP2) gene were identified. Further sequencing revealed a total of 11 CMT2 families with recessively inherited IGHMBP2 gene mutations. IGHMBP2 mutations usually lead to spinal muscular atrophy with respiratory distress type 1 (SMARD1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
105
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 50 publications
6
105
1
5
Order By: Relevance
“…Our results support the findings of Cottenie et al 7 and demonstrate 2 additional mutations in the IGHMBP2 gene associated with HMSN rather than SMARD1. Our findings suggest that genetic screening for IGHMBP2 mutations should be considered in patients with recessive HMSN.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Our results support the findings of Cottenie et al 7 and demonstrate 2 additional mutations in the IGHMBP2 gene associated with HMSN rather than SMARD1. Our findings suggest that genetic screening for IGHMBP2 mutations should be considered in patients with recessive HMSN.…”
supporting
confidence: 83%
“…5,6 However, a recent study revealed that truncating and missense mutations in IGHMBP2 could also lead to CMT. 7 Our proband presented with progressive weakness and sensory loss in distal limbs without any history of respiratory distress. As sensory neuropathy and history of respiratory distress are useful discriminating factors between HMSN and SMARD1, the clinical findings of this pedigree supported the diagnosis of HMSN rather than SMARD1.…”
mentioning
confidence: 99%
“…(7) However, in 2014, cases of patients from England, America, Serbia, Poland, Italy, Korea, and Vietnam were first described with a mutation in the same gene leading to the clinical presentation of HSMN2S (OMIM: 616155). (8) The young man turned to the doctor with complaints of a breathing disorder, which is typical for the clinical picture of spinal muscular atrophy with diaphragm paralysis. However, the conducted examinations showed no significant deviations from the norm.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in over 60 genes are known to be responsible for either the demyelinating or axonal subtypes of CMT; however, in spite of this number, a molecular diagnosis cannot be reached in approximately 75% of all axonal cases [14]. Mutations in IGHMBP2 had been exclusively associated with SMARD1 until a recent report by Cottenie et al [6] that identified patients with clinical features of CMT (sensorimotor axonal D.A. Dyment and H.J.…”
Section: Introductionmentioning
confidence: 96%
“…Mutations in this gene result in the degeneration of anterior horn cell alpha-motor neurons [4]. There is a spectrum of clinical presentations associated with mutations in IGHMBP2 [5][6][7][8][9][10][11], with individuals presenting with spinal muscular atrophy with respiratory distress (SMARD1; MIM# 604320) or Charcot-Marie-Tooth (CMT; MIM#616155) disease. SMARD1 is a rare autosomal recessive disorder that typically presents within the first two months of life and is characterized by respiratory failure, caused by diaphragmatic paralysis, and a severe infantile axonal neuropathy [5].…”
Section: Introductionmentioning
confidence: 99%